Rancang Bangun Mesin Pembuat Kerupuk Stik - Angga Iqbal Ababiel; Muhammad Anis Mustaghfirin; Dhika Aditya Purnomo (Proceedings Conference On Design Manufacture Engineering And Its Application, 2020)
Crackers are one of the snacks that are very popular with Indonesian people ranging from the lower classes to the upper middle class. One type of crackers made is stick crackers. Mr Suwarno's home industry in making stick crackers still uses a manual method which currently still adds a lot of time, cost and energy in making crackers. Therefore we need a stick cracker making machine as a helper to produce large products in order to get more products with faster time, labor is only at the operator and product output can be further increased. The method used by the author is the ulrich method by selecting several design concepts, design assisted by CAD software for making drawings, fabrication, assembly of machine components and testing tools to determine the production results of the machine. Based on the results of planning and design that has been done, the dimensions of the mixer and printer are produced with the main dimensions of 1350 mm x 360 mm x 840 mm. In testing the stick cracker making machine prototype can produce 30 kg in 1 hour.